DIETARY CARBOHYDRATE INTAKE AND FASTING BLOOD GLUCOSE AMONG PEOPLE VISIT NON-COMMUNICABLE DISEASE RISK FACTOR SURVEILLANCE IN PUSKESMAS KEDUNGMUNDU - Rohmah Kusuma Putri; Lintang Dian Saraswati; Mateus Sakundarno Adi (Jurnal Kesehatan Masyarakat (Undip), 2017)
Long lasting elevation of blood glucose concentrations, can result blindness, renal failure, vascular disease and neuropathy. Therefore, blood glucose concentration need to be maintained within narrow limits. The source of carbohydrate which has high dietary glycemic index causes stronger blood glucose response. The objective was to describe the dietary carbohydrate intake profile and fasting blood glucose profile among adult people. In this cross sectional study, the 100 subjects used were taken randomly from people who visit non communicable disease risk factor surveillance in PuskesmasKedungmundu, Semarang city. Fasting blood glucose was measured by glucose test strips and dietary carbohydrate intake was measured by 24 hours food recall. The data were analyzed using descriptive analysis by SPSS 20 and Nutrisurvey software. Results showed that the prevalence of impaired fasting glucose was 35%, and the prevalence of excess dietary carbohydrate intake was 17%, the average mean value of blood glucose among subjects was 104,20 mg/dl, while the mean of daily carbohydrate intake was 234,85 gram. The highest level of fasting blood glucose was 388 mg/dl and the lowest one was 60 mg/dl. The maximum value of carbohydrate consumption in one day was 481,70 gram while the minimum value was 80,30 gram. Reduction in carbohydrate intake in food and drink may be considered to decrease the problem of impaired fasting glucose.